Survival of nalidixic acid strains of Salmonella Enteritidis on mung bean sprouts and surfaces produced in a home-scale hydroponic system - Hernandez G., Elva A. (Zamorano: Escuela Agrícola Panamericana, 2024)
The production of sprouts in hydroponic systems is increasing worldwide, including alfalfa, mung bean, clover, etc., which are generally consumed raw or minimally processed. Mung bean sprouts are often contaminated with pathogens during production, one of the main pathogens is Salmonella Enteritidis. The presence of Salmonella in sprouts carries a high risk during their production as disinfection methods are often ineffective in inhibiting them. This study was based on examining the survival of Salmonella Enteritidis resistant to nalidixic acid in mung bean sprouts produced in hydroponic systems for 7 days under domestic conditions to evaluate its behavior. To evaluate this, mung bean seeds were grown in jars and exposed to distilled water contaminated with Salmonella at room temperature (25 °C) and 70% relative humidity. Samples were taken from the sprouts and surface of the jars and sown on xlt4 agar with nalidixic acid to detect only Salmonella. Salmonella Enteritidis was quantified by the plate count method and was detected at levels from 4 log CFU/g to 7 log CFU/g. Salmonella Enteritidis growth was higher in the sprouts than on the surface, reaching a level of 7.35 log CFU/g, however, on the surface there was growth, but it was not significant over time, reaching levels of 6.19 log CFU/mL. It was detected that Salmonella tends to move to surfaces through the water since seed rinsing is a risk of contamination of sprouts and surfaces by Salmonella Enteritidis under domestic conditions, so it is necessary that producers implement the requirements by the food safety rule focused on the production of sprouts.